Generation of a semi-dominant mutation with temperature sensitive effects on both locomotion and phototransduction in Drosophila melanogaster. - Watson, B.O.; Vilinsky, I.; Deitcher, D.L. (Journal of Neurogenetics, 2001)
A novel Drosophila mutant named Tripped-and-fell (Taf) was isolated in a F1 screen for dominant temperature sensitive paralytics. Recombination mapping using multiply marked chromosomes and P elements have pinpointed the locus of Taf to polytene band 93 on the right arm of the third chromosome (3R). When exposed to restrictive temperatures, both Taf heterozygotes and homozygotes paralyzed; however, homozygotes paralyzed at lower temperatures and took longer to recover than heterozygotes. There are also positive correlations between recovery time from paralysis and both duration and temperature of exposure. Electroretinograms (ERGs) revealed that both homozygotes and heterozygotes have a grossly normal light response at 22 degrees C, but at 37 degrees C, the ERGs from both homozygotes and heterozygotes are unable to maintain a normal sustained depolarization and have a reduced off-transient potential. The severity of the ERG repolarization phenotype is greater in homozygotes than in heterozygotes.